Bayesian Network Probability tables for Thumbnail Cache Identification - Morris, Sarah (Cranfield University, 2018)
Bayesian Network and Probability tables for Identatron. These are used for cluster sized thumbnail cache file fragment identification.
Keywords: 'Digital Forensics'; 'Bayesian Network'; 'classification approach generalizes'; 'Thumbnail cache'; 'Forensic Statistics'; 'Data Structures'